Psychosocial Characteristics and Gestational Weight Change among Overweight, African American Pregnant Women - Kelly C. Allison; Brian H. Wrotniak; Emmanuelle Paré; David B. Sarwer (Obstetrics and Gynecology International)
Objectives. To describe psychosocial factors identified as contributors of weight gain in the general population and to examine the relationship between these factors and gestational weight gain among low socioeconomic status, African American, overweight pregnant women. Methods. African American women (n=120) with a pregravid body mass index ≥25 kg/m2 completed measures of eating, sleep, and depressed mood between 14 and 24 weeks of gestation. Weight was tracked. Descriptive statistics, correlations, and linear regression modeling were used to characterize the sample and examine predictors of gestational weight gain. Results. Four percent screened positive for night eating syndrome, with 32% consuming at least 25% of their daily caloric intake after dinner (evening hyperphagia). None met criteria for binge eating disorder; 4% reported occasional binge episodes. Cognitive restraint over eating was low. Participants slept 7.1 (SD=1.9) h per night and reported 4.3 (SD=3.6) awakenings per week; 18% reported some level of depressed mood. Night and binge eating were related to each other, sleep quality, and depressed mood. Eating due to cravings was the only psychosocial variable to predict gestational weight gain. Conclusions. Depressed mood, night eating, and nighttime awakenings were common in this cohort, while cognitive restraint over eating was low. Most psychosocial variables were not predictive of excess gestational weight gain.